Calpain inhibition in a transgenic model of calpastatin overexpression facilitates reversal of myocardial hypertrophy - Sachse, Gregor; Tennigkeit, Johanna; Pagonas, Nikolaos; Hillmeister, Philipp; Buschmann, Ivo; Czolbe, Martin; Nordbeck, Peter; Schmitt, Joachim; Patschan, Daniel; Ritter, Oliver (ESC Heart Failure, 2025)
Aims It was recently demonstrated that the intracellular signalling phosphatase calcineurin is subject to cleavage by the protease calpain, resulting in a truncated calcineurin fragment that is a strong inductor of myocardial hypertrophy. We now address the question of whether inhibition of calpain function in cardiomyocytes, and thereby prevention of calcineurin truncation, attenuates development of myocardial hypertrophy. Methods and results We generated a transgenic mouse model with conditional cardiac calpastatin overexpression (CAST OE) and compared their cardiac hypertrophic response to angiotensin‐II (AngII) with that of non‐induced control animals. Angiotensin‐II osmotic mini‐pumps were removed 3 weeks after implantation and cardiac hypertrophy was re‐evaluated 3 weeks after pump removal. Induction of calpastatin overexpression resulted in 88% inhibition of calpain activity and suppressed calcineurin truncation. In CAST OE mice, basal phenotype and AngII‐induced myocardial hypertrophy were comparable with non‐induced controls (mean heart to body weight ratios ± SD in milligrams per gram: CAST OE, 4.8 ± 0.4; CAST OE + AngII, 7.1 ± 0.5; non‐induced, 4.9 ± 0.4; non‐induced + AngII, 7.2 ± 0.4). However, CAST OE mice demonstrated a complete reversal of hypertrophy when angiotensin‐II was removed, whereas hypertrophy persisted in non‐induced controls (CAST OE 5.0 ± 0.5; non‐induced 7.0 ± 0.4; P < 0.0001). Persistent hypertrophy in controls was accompanied by nuclear accumulation of truncated calcineurin and elevated activity of the Nuclear Factor of Activated T‐cells pathway. Moreover, we found that truncated calcineurin was insufficiently ubiquitinylated compared with its full‐length form and thus escaped degradation over several weeks in our in vivo experiments. Conclusions Our data demonstrate that calpain‐mediated cleavage results in nuclear accumulation of a truncated, constitutively active and degradation‐resistant calcineurin isoform that sustains a long‐term myocardial hypertrophic response to angiotensin‐II beyond withdrawal of the stimulus. Cardiomyocyte specific calpain inhibition by transgenic calpastatin overexpression prevented the post‐stimulus myocardial hypertrophic response.